Depression, anxiety, and post-traumatic stress disorder symptoms after hyperemesis gravidarum: a prospective cohort study. (12th December 2022) - Nijsten, Kelly; van der Minnen, Loïs M.; Dean, Caitlin; Bais, Joke M. J.; Ris-Stalpers, Carrie; van Eekelen, Rik; Bremer, Henk A.; van der Ham, David P.; Heidema, Wieteke M.; Huisjes, Anjoke; Kleiverda, Gunilla; Kuppens, Simone M.; et al.
Abstract: Objective: To determine the prevalence of depression, anxiety, and posttraumatic stress disorder (PTSD) years after hyperemesis gravidarum (HG) and its association with HG severity. Material and methods: This prospective cohort study consisted of a follow-up of 215 women admitted for HG, who were eligible to participate in a randomized controlled trial and either declined or agreed to be randomized between 2013 and 2016 in 19 hospitals in the Netherlands. Participants completed the Hospital Anxiety and Depression Scale (HADS) six weeks postpartum and during follow-up and the PTSD checklist for DSM-5 (PCL-5) during follow-up. An anxiety or depression score ≥8 is indicative of an anxiety or depression disorder and a PCL-5 ≥ 31 indicative of PTSD. Measures of HG severity were symptom severity (PUQE-24: Pregnancy Unique Quantification of Emesis), weight change, duration of admissions, readmissions, and admissions after the first trimester. Results: About 54/215 participants completed the HADS six weeks postpartum and 73/215 participants completed the follow-up questionnaire, on average 4.5 years later. Six weeks postpartum, 13 participants (24.1%) had an anxiety score ≥8 and 11 participants (20.4%) a depression score ≥8. During follow-up, 29 participants (39.7%) had an anxiety score ≥8, 20 participants (27.4%) a depression score ≥8, and 16 participants (21.9%) a PCL-5 ≥ 31. Multivariable logistic regression analysis showed that for every additional point of the mean PUQE-24 three weeks after inclusion, the likelihood of having an anxiety score ≥8 and PCL-5 ≥ 31 at follow-up increased with OR 1.41 (95% CI: 1.10;1.79) and OR 1.49 (95% CI: 1.06;2.10) respectively. Conclusion: Depression, anxiety, and PTSD symptoms are common years after HG occurred.